Smart receiver for multi-antenna transmitters with constellation shaping - Carvalho, Paulo Montezuma (2015)
Spectral and power efficiency together with physical layer security can be achieved by a MISO (Multiple Input Single Output) where multilevel modulations are decomposed as a sum of BPSK (Bi Phase Shift Keying) components that are combined at channel level. The directivity is associated to the transmitted information due to the shaping of the constellation in a desired direction Θ (it is important to note that shaping means a rearrangement of the constellation symbols according to a desired direction Θ) and can be be increased by changes on phases phase shifts between antenna array or changes on the values of the coefficients that define the BPSK components. Consequently, for successful data reception it is necessary to know the configuration parameters used at transmitter. Despite the security achieved by this transmitter structure, a practical application is only possible if authorized receivers are able to decode with success the transmitted data. Here it is demonstrated the validity of the hypothesis of a smart receiver that knows these parameters based on a algorithm that can estimate the set of coefficients applied in constellation shaping and the array configuration. The cases analyzed here and the simulation results presented show that good performance is attainable by the proposed receiver, even when the directivity increases with the number of BPSK components used in the decomposition of the multilevel constellation, which validate our initial assumption